(untitled) (Cardiovascular Journal, 2011)
Sudden withdrawal of oral anticoagulant in patients with metalic prosthetic valve without adequate coverage with parenteral heparin may lead to fatal consequences. Here the authors report a uncommon case of thrombotic mitral prosthetic occlusion due to sudden withdrawal of warfarin. Keywords: Prosthetic valve, Thrombus, Thrombolytic. DOI: http://dx.doi.org/10.3329/cardio.v1i1.8219 Cardiovasc. j. 2008; 1(1) : 109-111